Molecular and functional analysis of two new MTTP gene mutations in an atypical case of abetalipoproteinemia - Mathilde Di Filippo; Hervé Créhalet; Marie Elisabeth Samson-Bouma; Véronique Bonnet; Lawrence P. Aggerbeck; Jean-Pierre Rabès; Frederic Gottrand; Gérald Luc; Dominique Bozon; Agnès Sassolas (Journal of Lipid Research, 2012)
Abetalipoproteinemia (ABL) is an inherited disease characterized by the defective assembly and secretion of apolipoprotein B–containing lipoproteins caused by mutations in the microsomal triglyceride transfer protein large subunit (MTP) gene (MTTP). We report here a female patient with an unusual clinical and biochemical ABL phenotype. She presented with severe liver injury, low levels of LDL-cholesterol, and subnormal levels of vitamin E, but only mild fat malabsorption and no retinitis pigmentosa or acanthocytosis. Our objective was to search for MTTP mutations and to determine the relationship between the genotype and this particular phenotype. The subject exhibited compound heterozygosity for two novel MTTP mutations: one missense mutation (p.Leu435His) and an intronic deletion (c.619-5_619-2del). COS-1 cells expressing the missense mutant protein exhibited negligible levels of MTP activity. In contrast, the minigene splicing reporter assay showed an incomplete splicing defect of the intronic deletion, with 26% of the normal splicing being maintained in the transfected HeLa cells. The small amount of MTP activity resulting from the residual normal splicing in the patient explains the atypical phenotype observed. Our investigation provides an example of a functional analysis of unclassified variations, which is an absolute necessity for the molecular diagnosis of atypical ABL cases.